Use of lignocellulosic corn and rice wastes as substrates for oyster mushroom (Pleurotus ostreatus Jacq.) cultivation - Zárate-Salazar, Jhonatan Rafael; Santos, Mirela Natália; Caballero, Erik Nikol Muñoz; Martins, Olívia Gomes [UNESP]; Herrera, Ángel Alfonso Palomo (Springer Nature, 2020)
Abstract: The accumulation of agronomic wastes has caused several environmental problems, such as air and soil contamination, and insect and pathogen proliferation, among others. To mitigate this, studies have evaluated the use of these wastes as substrates for the cultivation of Pleurotus mushrooms, a low-cost/nutritionally important crop. This study aimed to evaluate the use of corn stubble and rice straw as substrates for the in vitro production of oyster mushrooms (Pleurotus ostreatus Jacq.) and the productive characterization (biological efficiency, production rate, earliness, daily productive capacity) of four isolated strains. The strains PO/A01, PO/A02, PO/A03, and PO/A04 were grown in Potato-Dextrose-Agar medium until complete colonization. The experiment was evaluated under a completely randomized design with 6 replications. Subsequently, the corn stubble and rice straw were disinfected, inoculated, bagged, incubated, and subjected to induction-fructification. The productive period ended after three harvests. At this stage, the experiment was conducted under a completely randomized design with a 4 × 2 factorial arrangement with 8 replications. The P. ostreatus strains inoculated in the corn stubble, compared to rice straw, showed 93.93% biological efficiency and a 2.07% production rate, representing increases of 30% and 50%, respectively. The strains PO/A03 and PO/A04 showed higher biological efficiency and organic matter loss. The PO/A02 strain showed greater earliness, with approximately 10 days to harvest. This study concluded that the isolated strains of P. ostreatus allow for the efficient use of corn stubble and rice straw, and can contribute to the management of agronomic wastes. Graphic abstract: [Figure not available: see fulltext.].
Keywords: Agronomic waste recycling; Biological efficiency; Earliness; Production rate